The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5688/ajpe7326
|View full text |Cite
|
Sign up to set email alerts
|

Intersession Remediation to Minimize Attrition in a Three-Year Pharmacy Program

Abstract: Objective. To describe an intersession remediation process in an accelerated three-year Doctor of Pharmacy (PharmD) program and to determine if the remediation process reduced attrition rates, including program withdrawals, progression to advanced pharmacy practice experiences (APPEs), and on-time graduation rates. Methods. Attrition was defined as dismissal, withdrawal, leave of absence, and/or change in graduation date. Progression data from students who matriculated between 2008 to 2016, with data available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Their findings revealed that students who enrolled in remedial courses demonstrated better academic performance than those who did not participate. Esposito et al ( 2019 ) conducted a study investigating the effects of a rigorous 2-week remediation program for students who had failed a final exam with a score that fell 10% or less below the cutoff grade. The program required eligible students to sign a written contract outlining a concentrated study plan that thoroughly assessed their strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings revealed that students who enrolled in remedial courses demonstrated better academic performance than those who did not participate. Esposito et al ( 2019 ) conducted a study investigating the effects of a rigorous 2-week remediation program for students who had failed a final exam with a score that fell 10% or less below the cutoff grade. The program required eligible students to sign a written contract outlining a concentrated study plan that thoroughly assessed their strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the intersession remediation strategy and rates of attrition at SU COPHS has been previously published. 4 The impact of intersession remediation as compared with course repeat or any other progression strategy on academic outcomes of interest, including professional licensure examinations, is not well-described in the literature. This may result from lack of standardization of remediation policies.…”
Section: Introductionmentioning
confidence: 99%
“…Available data appear to be in favor of a remediation model that offers individualized or focused support to students who are struggling, and this is included as a component of our intersession remediation strategy. 4 In a 2019 study by Coelho and colleagues, struggling dental students who accepted optional academic remediation based on poor performance on a progress examination had improved academic profiles compared to students who declined remediation. 6 A 2013 systematic review by Cleland and colleagues, which included 31 studies on remediation interventions for mostly medical students, noted the rarity of control/comparison groups, long-term followup measures, conceptual frameworks, and adequate sample sizes in the studies examined.…”
Section: Introductionmentioning
confidence: 99%